New antibacterial isocoumarin glycosides from a wetland soil derived fungal strain Metarhizium anisopliae. Issue 5 (1st March 2016) - Tian, Jie-Feng; Li, Peng-Ju; Li, Xiao-Xia; Sun, Ping-Hua; Gao, Hao; Liu, Xing-Zhong; Huang, Peng; Tang, Jin-Shan; Yao, Xin-Sheng
Graphical abstract: Abstract: Eight new isocoumarin glycosides (1 –8 ) were obtained from the solid culture of the wetland soil-derived fungus Metarhizium anisopliae (No. DTH12-10). Their chemical structures were elucidated by analyses of HR ESI-TOF MS, 1 H, 13 C NMR, 1 H– 1 H COSY, HSQC, and HMBC spectra. The absolute configurations were determined by single crystal X-ray diffraction, circular dichroism (CD) spectrum, and chemical derivatization methods. In addition, inhibition of the biofilm formation and the secretion of virulence factor of the new isocoumarin glycosides against Pseudomonas aeruginosa strain PAOA (clinical isolates) were evaluated. The result revealed that compound1 showed antibacterial activity comparable with ( Z )-4-bromo-5-(bromomethylene)-2(5 H )-furanone (BF).